Small molecule selectively suppresses MYC transcription in cancer cells - Bouvard, Claire; Lim, Sang Min; Ludka, John; Yazdani, Nahid; Woods, Ashley K.; Chatterjee, Arnab K.; Schultz, Peter G.; Zhu, Shoutian (NATL ACAD SCIENCES, 2017)
Stauprimide is a staurosporine analog that promotes embryonic stem cell (ESC) differentiation by inhibiting nuclear localization of the MYC transcription factor NME2, which in turn results in downregulation of MYC transcription. Given the critical role the oncogene MYC plays in tumor initiation and maintenance, we explored the potential of stauprimide as an anticancer agent. Here we report that stauprimide suppresses MYC transcription in cancer cell lines derived from distinct tissues. Using renal cancer cells, we confirmed that stauprimide inhibits NME2 nuclear localization. Gene expression analysis also confirmed the selective down-regulation of MYC target genes by stauprimide. Consistent with this activity, administration of stauprimide inhibited tumor growth in rodent xenograft models. Our study provides a unique strategy for selectively targeting MYC transcription by pharmacologicalmeans as a potential treatment for MYC-dependent tumors.
Keywords: EMBRYONIC STEM-CELLS; MURINE C-MYC; G-QUADRUPLEX; TRANSGENIC MICE; TUMOR MICROENVIRONMENT; NEOPLASTIC PHENOTYPE; LUNG-CANCER; PROMOTER; INHIBITION; EXPRESSION